2D Hydraulic Modelling of Dam Break Analysis Using MIKE FLOOD for Kenyir Dam - Rashid Mohd Shah M.; Mohd Sidek L.; Ruzaimei Yalit M.; Marufuzzaman M.; Basri H.; Kamal Yaacob M. (Springer, 2023)
Dams are large barriers built across rivers and streams in order to restrain and utilize the flow of water for numerous purposes like irrigation, generation of hydroelectricity and controlling the flood. Detention of water by large barriers creates lakes and reservoirs. However, a huge amount of water stored behind the dam can possess adverse effects on the downstream during the event of a dam break. It is very much essential for executing dam break studies to provide possible flood inundation information and impact assessment to the dam. This study was conducted to carry out hydraulic and dam break analysis of Kenyir Dam. Dam break modeling was performed under Probable Maximum Flood (PMF) scenario. MIKE 11 1-D model was used to derive breach outflow hydrograph, whereas MIKE 21 2-D model is being used for flood plain modeling and generation of inundations maps downstream of the dam. The routing of flow to the downstream area using MIKE FLOOD model was to obtain the flooded area, flood travel time and maximum flood depth. It was found from the PMF scenario, dam breach outflow hydrograph yielded the peak value of 468,352m3/s showed potential to flood the downstream area of the dam. This will result in identifying the affected location or villages located at the downstream of Kenyir Dam. Indirectly, it will become a reference for agencies such as Jabatan Pertahanan Awam (JPAM) and Jabatan Bomba dan Penyelamat Malaysia to take safety precautions during the happening of unwilling disaster. 2020, Springer Nature Singapore Pte Ltd.